Platelet specific knockout of integrin beta-3 (β3) reduces severity of necrotizing enterocolitis in murine neonates - Balamurugan, Marie Amalie; Ramatchandirin, Balamurugan; Desiraju, Suneetha; Subrramanya, Arjun; George Raj, Juanitaa; Ferris, Megan M.; Lawal, Zainab D.; Olaloye, Oluwabunmi O.; Konnikova, Liza; MohanKumar, Krishnan (Frontiers in Pediatrics, 2025)
IntroductionNecrotizing Enterocolitis (NEC) is the most impactful gastrointestinal disease of premature neonates and preclinical evidence shows that the event of platelet activation is an important pathophysiological contributor during NEC-like injury in murine neonates. Integrin αIIb/β3 (glycoprotein [GP]IIb/IIIa) is the primary platelet activation marker showing increased platelet-monocytes aggregation during NEC-like injury. The present study investigates whether platelet lineage-specific deletion of integrin-β3 reduces NEC-like injury in murine neonates.MethodsC57BL/6 and integrin-β3−/− mouse pups were subjected to trinitrobenzene sulfonic acid (TNBS)-induced NEC-like injury (n = 6/each group). Monocyte-platelet aggregation was measured by flow cytometry and immunofluorescence. Plasma levels of intestinal injury markers (FABP2, CRP, CXCL2 and SAA) and inflammatory cytokines (TNF-α, IL-1β, IL-6 and IL-1α) were measured by ELISA and multiplex array respectively. Intestinal inflammatory responses were confirmed by qRT-PCR.ResultsIntegrin-β3-associated platelet-monocyte aggregation was significantly observed in the intestine and blood of murine NEC-like injury and in the human NEC intestine. Platelet-specific deletion of integrin-β3's exon-1 leads to inhibition of platelet-monocyte aggregation in circulating blood and intestine, thus reducing the resulting intestinal injury and the level of inflammatory activation cytokines in the blood.ConclusionMonocyte-platelet aggregation is an important pathophysiological event and the blockade of integrin-β3 merits a potential therapeutic target in NEC.